خصوصية حق الانتفاع في قانون المعاملات المدنية الإماراتي - اللهيبي، صالح أحمد محمد عبطان; الشويهي، علي ارحمه علي (جامعة الشارقة, 2020)
حق الانتفاع من الحقوق العينية الأصيلة التي لم تنل حظها من البحث في دولة الإمارات العربية المتحدة من قبل الباحثين القانونين، عليه فقد وقع الاختيار على هذا العنوان، وقد حاولنا من خلال هذا البحث التمييز بين حق الانتفاع وحق المستأجر إذ وجدنا أن هذه من أكبر الإشكاليات التي لاحظناها في الواقع العملي، لاسيما إذا ما عرفنا أن هناك لجانا خاصة لفض النزاعات الإيجارية تختص في الفصل في نزاعات الإيجار، أما نزاعات حق الانتفاع فهي تبقى ضمن الولاية العامة للقضاء ومن اختصاص المحاكم الابتدائية. لذلك أثرنا اختيار هذا الموضوع وحاولنا التوصل إلى بعض الحلول التي سنبينها في البحث.
The right to benefit from the genuine rights in rem has not been adequately studied in the United Arab Emirates by law researchers. Hence, he title we have has been chosen for this paper. We have tried through this research to distinguish between the right of usufruct and the right of the tenant as one of the biggest problems we encountered in practice, bearing in mind that there are typical committees specialized in the settlement of rental and tenancy disputes. As or the disputes of usufruct rights, they remain within general jurisdiction, and more precisely the jurisdiction of lower courts. Therefore, we have raised this issue and tried to find some solutions that we will be exposed in the research.
Keywords: الدراسات القانونية -- قوانين المعاملات -- حق الانتفاع -- التشريعات والقوانين -- الإمارات العربية المتحدة